Penguatan Peran Ayah dalam Keluarga dan Masyarakat: Strategi Meningkatkan Kesadaran melalui Literasi dan Apresiasi Sosial - Paramitha, Ni Made Ayu Susanthi Pradnya; Dewi PF, Kadek Aria Prima; Mahardika, I Gusti Ngurah Agung Wijaya; Sentana, Gek Diah Desi; Suputra, I Kadek Darmo; Oktarina, Putu Santi; Krisdayanthi, Astrid; Perbowosari, Heny; Arini, Ni Wayan; Kristina, Ni Made Rai; Dewi, Putu Ayu Septiari; Dewi, Ni Luh PT. Putriyani; Wahyuni, Ni Nyoman Tri; Ariputra, I Putu Suyasa; Diaris, Ni Made; Dewi, Ni Made Umi Kartika; Sinarsih, Ni Ketut; Kantriani, Ni Ketut; Jaya, I Ketut Manik Asta; Mastini, Gusti Nyoman; Trisnadewi, Komang; Adnyani, Ni Wayan Satri; Lestari, Ni Gusti Ayu Made Yeni; Nerawati, Ni Gusti Ayu Agung; Premananda, Ni Luh Putu Uttari; Binawati, Ni Wayan Sariani; Kartika, Luh Gede Surya; Sukriani, Ni Luh; Permatasariid, I Gusti Agung Istri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The phenomenon of fatherlessness in Indonesia is an issue that cannot be ignored, considering the importance of the role of fathers in character formation, emotional well-being, and family economic stability. The figure of the father not only functions as a breadwinner, but also as an educator, role model, and the main supporter in the development of children. Active father involvement contributes to the child's psychological balance, preventing negative impacts such as low self-confidence, difficulties in building social relationships, and an increased risk of mental problems. In addition, the role of men in society also contributes to community strengthening and inclusive social development. This service activity aims to increase public awareness of the importance of the presence and involvement of fathers and men in family and social life. One form of implementation of this program is the organization of a letter writing competition for fathers as a medium of reflection and appreciation. This activity is expected to be able to build collective awareness about the importance of the father figure, strengthen emotional relationships in the family, and encourage the community to appreciate the role of men in various aspects of life. Thus, this activity contributes to building a culture of appreciation for the role of fathers and encourages the active participation of men in forming a more harmonious family and community.